Pengaruh Nilai Nasabah, Corporate Image, Dan Relationship Marketing Terhadap Kepuasan Nasabah Pada PT. BPD Jawa Timur (Bank Jatim) Kota Probolinggo - Putri Pramana, Zalfa Nur Auliya; Elmas, Muhammad Syarif Hidayatullah; Priantono, Seger (Universitas Panca Marga, 2024)
Customer satisfaction is a feeling of pleasure or displeasure with a product or service from a company. This study aims to analyze the effect of customer value, corporate image, and relationship marketing on customer satisfaction partially and determine the strongest variable on customer satisfaction. This research method uses quantitative with an associative approach. The population of this study were all active customers of PT Bank Jatim Probolinggo City. A total of 112 active customers of PT Bank Jatim in Probolinggo City were taken as samples with purposive sampling. Data collection through questionnaires. Data analysis techniques through validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results showed that customer value has a significant effect on customer satisfaction, corporate image has a significant effect on customer satisfaction, and relationship marketing has a significant effect on customer satisfaction. The most powerful variable in this study is relationship marketing.